A Cross-sectional study to assess the Level of knowledge of Youths aged 18-35 regarding negative Consequences of Cigarette smoking at Napier market, Jinja City. - Moses Hajusu Mangeni; Sam Wanyonyi; Boniface Ogwok; Harriet Anamo; Edmond Okello; Michael Albert Olinga (Student's Journal of Health Research Africa, 2022)
Background: